A survey of the European Reference Network EpiCARE on clinical practice for selected rare epilepsies. Issue 1 (13th January 2021) - Baumgartner, Tobias; Carreño, Mar; Rocamora, Rodrigo; Bisulli, Francesca; Boni, Antonella; Brázdil, Milan; Horak, Ondrej; Craiu, Dana; Pereira, Cristina; Guerrini, Renzo; San Antonio‐Arce, Victoria; Schulze‐Bonhage, Andreas; et al.
Abstract: Objective: Clinical care of rare and complex epilepsies is challenging, because evidence‐based treatment guidelines are scarce, the experience of many physicians is limited, and interdisciplinary treatment of comorbidities is required. The pathomechanisms of rare epilepsies are, however, increasingly understood, which potentially fosters novel targeted therapies. The objectives of our survey were to obtain an overview of the clinical practice in European tertiary epilepsy centers treating patients with 5 arbitrarily selected rare epilepsies and to get an estimate of potentially available patients for future studies. Methods: Members of the European Reference Network for rare and complex epilepsies ( EpiCARE) were invited to participate in a web‐based survey on clinical practice of patients with Dravet syndrome, tuberous sclerosis complex (TSC), autoimmune encephalitis, and progressive myoclonic epilepsies including Unverricht Lundborg and Unverricht‐like diseases. A consensus‐based questionnaire was generated for each disease. Results: Twenty‐six of 30 invited epilepsy centers participated. Cohorts were present in most responding centers for TSC (87%), Dravet syndrome (85%), and autoimmune encephalitis (71%). Patients with TSC and Dravet syndrome represented the largest cohorts in these centers. The antiseizure drug treatments were rather consistent across the centers especially with regard to Dravet syndrome, infantile spasms in TSC, and Unverricht Lundborg / Unverricht‐like disease. Available, widely used targeted therapies included everolimus in TSC and immunosuppressive therapies in autoimmune encephalitis. Screening for comorbidities was routinely done, but specific treatment protocols were lacking in most centers. Significance: The survey summarizes the current clinical practice for selected rare epilepsies in tertiary European epilepsy centers and demonstrates consistency as well as heterogeneity in the treatment, underscoring the need for controlled trials and recommendations. The survey also provides estimates for potential participants of clinical trials recruited via EpiCARE, emphasizing the great potential of Reference Networks for future studies to evaluate new targeted therapies and to identify novel biomarkers.